Influence of Damage of the Winter Cutworm on the Yield of Cotton - Tukhtaev Shonazar Khozhievich; Ganieva Feruza Amrilloevna; Mukhammedova Gulasal Normuhammad qizi (Zien Journals, 2022)
In the conditions of the Bukhara region of the Peshku district, cotton is damaged by more than 200 types of pests. Among them, the most common is the winter cutworm, the harmfulness of which reaches 18%. To save cotton from damage by the winter scoop, a complex system of measures is used, among which the leading place is occupied by agrotechnical and chemical methods of control.
Keywords: winter cutworm; agricultural practices; harmfulness; damage